Influence of Quality of work life and Teamwork on Employee Commitment of Employee in Department of Engineering of a Maintenance and Engineering Business Company in Eastern Region - Sutthiprapa, Nutcha; Chaiyakul, Thitima (Journal for Developing the Social and Community, 2026)
Background and Objectives: The engineering and maintenance business is one of the businesses that plays an important role in the development of the industry in the eastern part of Thailand. However, the high turnover rate of 17.4 percent reflects the problem of organizational engagement that needs to be addressed. The purpose of this research was to study (1) the level of quality of life at work; (2) the influence of quality of work life on organizational engagement, and (3) the influence of teamwork on organizational engagement. Research methodology: This research is a quantitative study. The sample was 283 employees in the engineering sector. The sample size was determined using Taro Yamane’s formula and stratigraphic sampling. The tool used was a 5-level estimator questionnaire, which was checked for content accuracy by 3 experts (IOC = 0.67-1.00) and had a confidence value of 0.92. Main results: The results showed that the level of employee opinion on the quality of life at work Teamwork and a large level of commitment to the organization as a whole. Quality of life at work in 7 areas, including work that is beneficial to society (β=0.301) Work and overall lifestyle (β=0.223) Fair and adequate remuneration (β=0.194) Environmentally Safe (β=0.193) Opportunities to develop and use individual abilities (β=0.158) Participation in work and relationships with others (β=0.156) and personal rights at work (β=0.138) All had a statistically significant positive influence on organizational engagement at the level of 0.01, with 65.1% of the participants able to predict organizational engagement, while teamwork in four areas: leadership distribution (β=0.361); Shared decision-making (β=0.313) Mission and goal setting of the team (β=0.255) and open communication (β=0.165) There was a statistically significant positive influence on organizational engagement at the level of 0.01, with 57.2% of the forecasts being able to participate in the forecast. Conclusions: The results of the study suggest that both quality of life at work and teamwork are important factors that positively influence employee engagement with the organization in the engineering and maintenance business. Formulation of policies that focus on improving the quality of life at work. Especially in the field of work that is beneficial to society and work-life balance. Along with promoting teamwork through the systematic distribution of leadership and collaborative decision-making. It will be able to strengthen the commitment of employees to the organization to be stable and sustainable. This will positively affect the overall performance of the enterprise and support the long-term development of the industrial sector.